2016
DOI: 10.1021/acsami.6b04035
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of Stages in the Microstructure Evolution in Copper under Mild Reciprocating Tribological Loading

Abstract: Tailoring the surface properties of a material for low friction and little wear has long been a goal of tribological research. Since the microstructure of the material under the contact strongly influences tribological performance, the ability to control this microstructure is thereby of key importance. However, there is a significant lack of knowledge about the elementary mechanisms of microstructure evolution under tribological load. To cover different stages of this microstructure evolution, high-purity cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
88
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 49 publications
16
88
2
Order By: Relevance
“…[66] Focused ion beam cross-sections for all cycle numbers from the middle of the wear tracks are presented as cross-sectional SEM images in Figure 8. A fundamental understanding of the elementary mechanisms acting at different stages of the microstructural evolution is still lacking.…”
Section: Cyclic Loading and Microstructure Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…[66] Focused ion beam cross-sections for all cycle numbers from the middle of the wear tracks are presented as cross-sectional SEM images in Figure 8. A fundamental understanding of the elementary mechanisms acting at different stages of the microstructural evolution is still lacking.…”
Section: Cyclic Loading and Microstructure Evolutionmentioning
confidence: 99%
“…The microstructural investigations were based on focused ion beam (FIB) and scanning electron microscopy (SEM) in combination with cross-sectional EBSD. [66] Focused ion beam cross-sections for all cycle numbers from the middle of the wear tracks are presented as cross-sectional SEM images in Figure 8.…”
Section: Cyclic Loading and Microstructure Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, the elementary mechanisms governing the early stages of tribological loading have been studied less extensively, even though they seem elemental in deciding the future fate of a tribological contact. We have previously reported a distinct horizontal line feature at a uniform depth of about 150 nm below the surface of copper samples contacted in dry sliding conditions by a sapphire sphere 12 . Since this line was found to consist of dislocations, it was named dislocation trace line (DTL).…”
mentioning
confidence: 94%
“…More interestingly, pure metals exhibit an apparent bi-stability in their friction behavior, where in contact conditions associated with low friction the trends in friction appear to be converging, while the trends diverge for higher friction. Various authors [8,[10][11][12][13][14][15] have reported that this unusual and highly desirable macro-scale behavior for pure metals and alloys are associated with the formation and persistence of a thin layer of highly refined, ultra-nanocrystalline (10 to 20 nm grain size) metal at the sliding surface, though the conditions and mechanism through which this layer is formed and how these two characteristics are correlated remains unclear. We propose a hypothesis and supporting evidence for a correlation between surface grain structure evolution and friction behavior of metals that is both predictive and quantitative, relying exclusively on materials properties and contact mechanics models to predict the bounds of observed friction regimes.…”
Section: Introductionmentioning
confidence: 99%